2021
DOI: 10.1039/d0cc06172g
|View full text |Cite
|
Sign up to set email alerts
|

Highly convenient and highly specific-and-sensitive PCR using Se-atom modified dNTPs

Abstract: Primer design and condition optimization for PCR are tedious and labour-intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In order to investigate the mechanism of the de novo DNA synthesis, we have explored the polymerization with the modified dNTPs (Figure ). We have discovered that the de novo synthesis with polymerases (Pol I, Bst, and Taq functioning under 37, 63, and 72 °C, respectively) can be inhibited by the modified dNTPs (such as dNTPαSe; Figure B). Furthermore, we have found that although the polymerase generates byproduct DNAs more and faster in the presence of the nickase than its absence, dNTPαSe can inhibit the byproduct polymerization as well (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the mechanism of the de novo DNA synthesis, we have explored the polymerization with the modified dNTPs (Figure ). We have discovered that the de novo synthesis with polymerases (Pol I, Bst, and Taq functioning under 37, 63, and 72 °C, respectively) can be inhibited by the modified dNTPs (such as dNTPαSe; Figure B). Furthermore, we have found that although the polymerase generates byproduct DNAs more and faster in the presence of the nickase than its absence, dNTPαSe can inhibit the byproduct polymerization as well (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proposed one-pot detection method that could complete virus detection in one single tube ( Chen et al, 2020a ; Ding et al, 2020 ; Pang et al, 2020 ). However, the detection sensitivity is compromised somehow due to the generation of contaminated nucleic acids, which creates urgent needs for developing contamination-free detection such as high specificity gene amplification technology ( Hu et al, 2021 ). The most feasible strategy for integrating CRISPR-Cas systems with another technology or system is to find a specific nucleic acid molecule as a linker.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…[4][5][6][7] Recently, Huang and coworkers found that dNTPαSe substrates can significantly improve specificity and enhance sensitivity of polymerase chain reaction (PCR) via inhibiting nonspecific polymerization, which could greatly facilitate PCR amplification, therapeutic discovery, and X-ray structural studies. [8,9] In addition, NTPαXs are also valuable in medicinal chemistry. Shaw and Fischer have shown that α-P-BH 3 -modified triphosphates of antiviral nucleosides and adenosine analogues are potent HIV-1 transcriptase inhibitors [10] and P2Y 1 receptor agonists, [11] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to β‐ and γ‐ P ‐modified NTPs, the most distinct feature of NTPαXs is that they could be recognized by polymerases to incorporate S, Se, and BH 3 ‐modified phosphate linkages into DNA and RNA, which has made NTPαXs versatile tools in molecular biology [4–7] . Recently, Huang and coworkers found that dNTPαSe substrates can significantly improve specificity and enhance sensitivity of polymerase chain reaction (PCR) via inhibiting nonspecific polymerization, which could greatly facilitate PCR amplification, therapeutic discovery, and X‐ray structural studies [8,9] . In addition, NTPαXs are also valuable in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%